A Pharmacist‐Led Program to Evaluate and Reduce Polypharmacy and Potentially Inappropriate Prescribing in Older HIV‐Positive Patients. Issue 12 (30th November 2017) - McNicholl, Ian R.; Gandhi, Monica; Hare, C. Bradley; Greene, Meredith; Pierluissi, Edgar
Abstract : Objective: The goal of this pharmacist‐led study was to utilize two validated instruments, Beers Criteria and Screening Tool of Older Persons' Potentially Inappropriate Prescriptions (STOPP), to assess potentially inappropriate prescribing (PIP) in older patients infected with the human immunodeficiency virus (HIV) and evaluate pharmacist interventions. Design: Prospective randomized interventional trial. Setting: Large urban clinic providing interdisciplinary primary and HIV care for 2700 HIV‐positive publicly insured patients. Data Source: A computerized electronic record search was conducted for all patients who met the two search criteria: 50 years and older, and a primary care appointment within the last 12 months. Patients: After identification of 857 patients meeting the search criteria, 324 patients were randomly selected and contacted, resulting in 248 patients assessed. Measurements and Main Results: Patients had a mean age of 58 years, 71% male, 44% white, and a mean CD4 count of 536 cells/mm 3 . Common comorbidities included hypertension (56%), depression (52%), asthma/chronic obstructive pulmonary disease (48%), dyslipidemia (39%), coronary artery disease (27%), and diabetes (22%). Patients sampled were prescribed a mean of 11.6 ± 5.7 concomitant medications (excluding antiretrovirals) with 35% receiving at least 16 medications. PIP was identified in 54% and 63% of patients using the STOPP and Beers Criteria, respectively. Twenty‐five contraindicated drug interactions were identified in 20 patients. After the pharmacist visit, at least 69% of patients had at least one medication discontinued with almost 10% having six or more medications discontinued. More than 40% of patients had at least one Beers or STOPP criteria that required immediate correction by the pharmacist. Conclusions: Results suggest that targeting individuals with 11 or more chronic medications would have the highest yield and greatest impact. Pharmacist‐led review of medication prescribing using Beers and STOPP criteria revealed a large number of PIP, many amenable to immediate clinical pharmacist intervention.